ENHANCING STUDENT’S PRODUCTIVITY IN THE POST-PANDEMIC ERA WITH THE PRINCIPLE OF BEHAVIOR CHANGE - Devanny Gumulya (Jurnal Imagine, 2022)
One of the issues encountered during the COVID-19 pandemic was a decline in productivity levels. It is undeniable that differences in facilities and activities have a significant impact on productivity. Work and study activities must be adapted under new work environment (at home). Both activities performed together with other activities at home. Negative habits will emerge if the individual does not adapt properly, which can interfere with work or study activities. The emergence of new negative habits can reduce an individual's productivity. According to Tali Sharot's psychological theory, three positive strategies are required to change negative behavior: social incentives, immediate rewards, and progress monitoring. The study's results a product design proposal: a mobile application and watches that use Bluetooth networks. Both are designed to track students' productivity by implementing the three strategies of behavior change theory.